Strategi Manajemen Pemasaran Destinasi Pariwisata Berkelanjutan: Suatu Kajian Literatur - Edi Irawan (Lembaga Pengembangan Kinerja Dosen, 2023)
This article reviews and attempts to confirm the marketing management strategy for sustainable tourism destinations. In the marketing management of tourism destinations, it is necessary to carry out good planning that involves the role of the central government, regional governments, the private sector, business actors and the surrounding community. In planning it is necessary to carry out an analysis, namely: (a) Analysis of the macro environment which includes the political, economic, social, legal and cultural environment;,(b) Analysis of the microenvironment including producers, supplier, competitors, tourists and community; (c) Competitor analysis including similar tourits destinations, and (d) Market analysis, namely the potential of tourists and the tourist market. The marketing strategy consists of analysis, development, implementation and evaluation of activities in the development of tourist destinations. Likewise in the development of sustainable tourism management there are several aspects that need to be considered, namely; (a) Aspects of the attractiveness of tourist attractions; (b) Access to tourist spots; (c) Main and supporting facilities such as hotels, restaurants and others; and (d ) Institutions such as travel agents, travel agents, tours guides and others.